A study on wing morphology of avifauna community - Izwan Asraf, Md Zin. (Universiti Malaysia Sarawak (UNIMAS), 2007)
Wing loading and aspect ratio are important in determining the ecological adaptation of avifauna community. Wing loading determines the power needed to fly while aspect ratio determines the agility and manoeuvrability of the birds. This study was conducted in Bako National Park and Kubah National Park. A total of 249 birds representing 17 families were analysed and there are significance differences between aspect ratio and wing loading among the families. From this study, it can be concluded that birds that have high wing loading value are often found in open habitat. While, birds that have low wing loading value are often found in denser habitat. Birds that have rounded wings usually have long aspect ratio. While birds that have long and slender wings have higher aspect ratio. These are the characteristics that are useful in determining the habitat of a birds. However, many other aspects should be considered in understanding the wing morphology ofthe birds.